Study of polarization rotator - Ho, Sheng Yu (2018)
Polarization rotator can manipulate electromagnetic wave rotate linear plane waves by 90 degrees. There are various design exists in the literature review, in one study, a multilayer polarization rotator was able to rotate linear plane wave of frequencies from 4.4GHz to 12 GHz at 92% transmission coefficient [1]. Another study has demonstrated that linear plane waves can be rotated using three layers of split-ring polarizer with frequencies from transmission coefficient [2]. Simulation and observation have been conducted on one of the polarization design [1]. The observation will assist the student to improve a polarization rotator. The student design a polarization with the bandwidth of 3.86 to 14.95 GHz, with a fractional bandwidth of 117.95%, which is 33.05% better than the original design. A prototype have been fabricated and compared to the simulation results. The measurement seem to be in agreement of the simulation results.